Research Note: Benefits and Drawbacks of Pre-bloom Applications of Gibberellic Acid (GA3) for Stem Elongation in Sauvignon blanc - Molitor, D.; Behr, M.; Hoffmann, L.; Evers, D. (South African Journal of Enology and Viticulture, 2016)
Dense grape clusters have a high predisposition to bunch rot. An elongation of cluster stems could result in a loosening of the cluster structure. To achieve such an elongation, gibberellic acid (GA3; 10 ppm) was applied to Sauvignon blanc either when three, five, seven, nine, 11 or 13 leaves were unfolded or at full bloom in the 2010 season. In the present season, all applications led to stem elongation, a reduction of cluster compactness as well as a reduction of bunch rot severity. The density index proved to be an efficient tool to describe the predisposition of grape clusters to bunch rot. Best success was achieved if the application took place when seven leaves were unfolded. In the subsequent season (2011; the year following the year of application), the number of inflorescences per shoot, the length of the clusters, as well as the yield were considerably reduced, especially in the treatments with promising positive effects on the cluster structure and disease severity. Hence, the present study shows the loosening potential as well as the risk of pre-bloom gibberellic acid applications. Due to the observed negative resultant effects, the pre-bloom application of GA3 at the present concentration (10 ppm) cannot yet be recommended for practical use in Sauvignon blanc.